Malignant melanoma in Bari. Epidemiological data. - Bonifazi, E.; Ciampo, L.; Berloco, A.; Lospalluti, L.; Conca, R.; Ferrante, M.; Maccuri, A.; Pollice, L.; Ricco, L.; Bilancia, M.; Albrizio, M.; Lospalluti, M. (European Journal of Pediatric Dermatology, 2001)
Epidemiological data regarding 1,504 cases of primary malignant melanoma of the skin removed and diagnosed in Bari from 1975 to 2000 are reported. Particularly, besides the total number of cases, figures per year, sex, age and site of the primary tumor are reported. The prevalence of melanoma is increasing even in Bari of about 10% per year. Females (55%) are affected slightly more frequently than males. With regard to the age, the most affected five-year period is between 56 and 60, with 75% of cases included between 36 and 75 years. Three cases of prepubertal melanoma with a prevalence of 0.2% of the cases are reported. Particular attention was paid to the different distribution per site according to the sex. Once confirmed the more frequent involvement of the lower limb in females and of the trunk in males, we subdivided in age groups the cases of melanoma. We showed that this different localization in the two sexes starts after 30 years and persists after 60 years. As the more frequent localization on the lower limb in the female lacks in the 16-30 age group and on the other hand is present in the over sixty age group, the involvement of this site is probably not exclusively related to sex-linked hormonal factors.